2021
DOI: 10.1126/sciadv.abd6187
|View full text |Cite
|
Sign up to set email alerts
|

The keratin network of intermediate filaments regulates keratinocyte rigidity sensing and nuclear mechanotransduction

Abstract: The keratin network of intermediate filaments provides keratinocytes with essential mechanical strength and resilience, but the contribution to mechanosensing remains poorly understood. Here, we investigated the role of the keratin cytoskeleton in the response to altered matrix rigidity. We found that keratinocytes adapted to increasing matrix stiffness by forming a rigid, interconnected network of keratin bundles, in conjunction with F-actin stress fiber formation and increased cell stiffness. Disruption of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 55 publications
0
56
0
Order By: Relevance
“…Interestingly, the K14 keratin cytoskeleton is deformed less when keratinocytes are on stiff substrates (70 and 214 kPa) compared to a soft one (8 kPa). The Young's modulus (stiffness) showed a progressive increase with substrate stiffness [94]. Similarly, Young's moduli of cells with and without vimentin also depend on substrate stiffness [95].…”
Section: In Situ Mechanical Probing Of If Network In Cells and Nucleimentioning
confidence: 91%
“…Interestingly, the K14 keratin cytoskeleton is deformed less when keratinocytes are on stiff substrates (70 and 214 kPa) compared to a soft one (8 kPa). The Young's modulus (stiffness) showed a progressive increase with substrate stiffness [94]. Similarly, Young's moduli of cells with and without vimentin also depend on substrate stiffness [95].…”
Section: In Situ Mechanical Probing Of If Network In Cells and Nucleimentioning
confidence: 91%
“…During the data post-processing steps, the pixels on each grid were classified and split as belonging to the cell or the gelatin substrate based on their measured height, using Otsu’s method for image thresholding ( Laly et al, 2021 ). Subsequent force-indentation curve analysis was dependent on whether a given pixel had been classified as “gel” or “cell.” For “gel” pixels, the force-indentation curves were analyzed using Bilodeau’s model for a conical indenter.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the recent introduction of force-feedback modalities in commercial AFMs allows mapping not only the cell topography, but also simultaneously all the mechanical properties listed above. Therefore, by performing force-feedback imaging on sparsely cultured cells and then using the topography map to threshold the obtained maps based on height, we can not only measure mechanical properties of the cells, but also simultaneously those of their neighboring ECM ( Laly et al, 2021 ). Put together, the convergence of recent advances in AFM operating modalities, contact mechanics modeling and force-indentation data analysis allows us for the first time to develop a robust multiparametric approach to characterize the mechanical changes of differentiating cells and their underlying ECM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AFM analysis of human KCs showed that cortical tension in the actin cytoskeleton regulates the movement of cells from the basal to suprabasal layer and helps to maintain tissue homeostasis (Miroshnikova et al, 2018). Moreover, by varying the depth and force of indentation, it is possible to inspect the stiffness of subcellular structures such as the lipid bilayer, cornified envelope, cytoskeleton, and nucleus (Laly et al, 2021;Milani et al, 2018). Complementing the in vitro cellular studies, AFM has also been employed to map the elastic moduli across the different layers of plantar and nonplantar skin in a crosssectionally cut tissue, and the plantar skin cells of the stratum corneum, epidermis, and dermis were shown to be stiffer and less deformable (Boyle et al, 2019).…”
Section: Applications Of Afm In Skin Science and Dermatologymentioning
confidence: 99%
“…Our team has recently extended the application of AFM analysis of keratin mechanics by combining indentation experiments with time-lapse fluorescence imaging of GFP-tagged K14. In this experiment, we can directly measure the deformation of the keratin network by particle image velocimetry on indentation with the AFM tip, and this method has allowed us to quantify how the keratin cytoskeleton mechanically adapts to altered mechanical environments (Laly et al, 2021). The role of keratins and specific intercellular adhesion complexes behind desmosomal pathologies has also been examined by combining AFM with molecular recognition approaches to measure adhesive properties of desmosomal cadherins such as desmoglein 3 (DSG 3) associated with the blister-forming autoimmune disease pemphigus vulgaris (Vielmuth et al, 2018).…”
Section: Applications Of Afm In Skin Science and Dermatologymentioning
confidence: 99%